2005
DOI: 10.1111/j.1464-410x.2005.05678.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the biological features between prostate cancers arising in the transition and peripheral zones

Abstract: Ki-67, Bcl-2, matrix metalloproteinase-2 (MMP-2), MMP-9 and vascular endothelial growth factor (VEGF). RESULTSTwenty-four patients were diagnosed as having TZ cancer and the remaining 100 as having PZ cancer. Prostate specific antigen (PSA) values in patients with TZ cancer were significantly higher than in those with PZ cancer. Tumour volume in TZ cancer was significantly greater than that in PZ cancer, but there was no significant difference in biochemical recurrence-free survival between the groups. Immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 20 publications
(36 reference statements)
1
38
0
1
Order By: Relevance
“…Previous comparisons of peripheral-and transition-zone cancers have given conflicting results. Cancers arising in these two zones have distinct morphological and immunohistochemical characteristics and it has been reported that transition-zone cancers are associated with more favourable pathological features (Grignon and Sakr, 1994;Greene et al, 1995;Sakai et al, 2005). In contrast, as judged by biochemical recurrence, there appeared to be no difference in outcome between transition-zone and peripheral-zone cancers following prostatectomy (Sakai et al, 2005;Chun et al, 2007).…”
Section: Ets Gene Rearrangements In Prostate Tissues J Clark Et Almentioning
confidence: 65%
“…Previous comparisons of peripheral-and transition-zone cancers have given conflicting results. Cancers arising in these two zones have distinct morphological and immunohistochemical characteristics and it has been reported that transition-zone cancers are associated with more favourable pathological features (Grignon and Sakr, 1994;Greene et al, 1995;Sakai et al, 2005). In contrast, as judged by biochemical recurrence, there appeared to be no difference in outcome between transition-zone and peripheral-zone cancers following prostatectomy (Sakai et al, 2005;Chun et al, 2007).…”
Section: Ets Gene Rearrangements In Prostate Tissues J Clark Et Almentioning
confidence: 65%
“…16 In addition, transition zone tumors also express lower levels of p53 and bcl-2 than peripheral zone tumors. 16,17 These intrinsic biological difference between transition zone and peripheral zone tumors may also contribute to their different clinical behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Some studies have suggested that there are differential expression levels of proliferative genes and oncogenes between transition and peripheral zone tumors, which may contribute to their clinical and biological differences. [14][15][16][17] However, to our knowledge, the role of TMPRSS2-ERG gene fusion in the zonal origin of prostate cancer has not been studied. In this study, we evaluated the TMPRSS2-ERG gene fusion in prostate cancers arising from the transition zone in comparison with those arising from the peripheral zone.…”
mentioning
confidence: 99%
“…The peripheral zone (PZ) is the area where most prostate cancers grow [3]. Moreover, cancers of these two zones exhibit different behaviors [4]. Thus, it appears important to separate them in order to apply different analysis algorithms.…”
Section: Introductionmentioning
confidence: 99%